Comprehensive Evaluation of the Hydrocarbon Preservation Conditions in the Complex Tectonic Area of the Southwestern Sichuan Basin, China. (18th April 2023) - Fan, Cunhui; Cao, Huwei; Li, Jing; Xia, Maolong; Liu, Jing; Liang, Jing; Meng, Lifeng; Zhu, Haihua
Abstract : There are various styles of faults, folds, and unconformity structures in the southwestern Sichuan Basin, which have an important impact on hydrocarbon preservation. Based on the data of regional geological, seismic, formation water characteristics, caprock characteristics, and production, the hydrocarbon preservation conditions of the key horizons (Cambrian, Upper Permian, and Triassic) were analyzed. Southwestern Sichuan Basin margin structure has two obvious tectonic layers (the upper and lower). The upper tectonic layer is dominated by Middle Triassic detachment faults and derived thrust faults, while the lower tectonic layer has concealed structures composed of basement detachment faults and derived thrust faults. There are mainly NE, near-SN, NW, and near-EW faults. The outcrops are in the Middle-Cenozoic strata, changing from old to new from outside the Basin to inside the Basin. There are three main sets of high-quality caprocks, i.e., the mudstone of the bottom of the Xujiahe Formation, the gypsum-salt rocks of the Middle-Lower Triassic, and the Lower Cambrian mudstone. Based on the faults, outcrops, formation water type, mineralization, and caprock characteristics, the hydrocarbon preservation evaluation system was established, which divides into the areas of Class I, II, and III. The distribution range of the favorable areas of different horizons has good inheritance, and the hydrocarbon preservation conditions gradually improve from outside the basin to inside the basin. Class I favorable areas are the most widely distributed and are mainly located within the basin, with the characteristics of a low degree of fault development, relatively new outcropping strata, CaCl2 formation water type, and large caprock thickness.